In-depth genome analyses of viruses from vaccine-derived rabies cases and corresponding live-attenuated oral rabies vaccines. Issue 33 (2nd August 2019) - Pfaff, Florian; Müller, Thomas; Freuling, Conrad M.; Fehlner-Gardiner, Christine; Nadin-Davis, Susan; Robardet, Emmanuelle; Cliquet, Florence; Vuta, Vlad; Hostnik, Peter; Mettenleiter, Thomas C.; Beer, Martin; Höper, Dirk
Abstract: Live-attenuated rabies virus strains such as those derived from the field isolate Street Alabama Dufferin (SAD) have been used extensively and very effectively as oral rabies vaccines for the control of fox rabies in both Europe and Canada. Although these vaccines are safe, some cases of vaccine-derived rabies have been detected during rabies surveillance accompanying these campaigns. In recent analysis it was shown that some commercial SAD vaccines consist of diverse viral populations, rather than clonal genotypes. For cases of vaccine-derived rabies, only consensus sequence data have been available to date and information concerning their population diversity was thus lacking. In our study, we used high-throughput sequencing to analyze 11 cases of vaccine-derived rabies, and compared their viral population diversity to the related oral rabies vaccines using pairwise Manhattan distances. This extensive deep sequencing analysis of vaccine-derived rabies cases observed during oral vaccination programs provided deeper insights into the effect of accidental in vivo replication of genetically diverse vaccine strains in the central nervous system of target and non-target species under field conditions. The viral population in vaccine-derived cases appeared to be clonal in contrast to their parental vaccines. The change from a state of high population diversity present in the vaccine batches to a clonal genotype in the affected animal may indicate the presence of a strong bottleneck during infection. In conclusion, it is very likely that these few cases are the consequence of host factors and not the result of the selection of a more virulent genotype. Furthermore, this type of vaccine-derived rabies leads to the selection of clonal genotypes and the selected variants were genetically very similar to potent SAD vaccines that have undergone a history of in vitro selection.